The effectiveness of Konjo traditional game “Ak Bombo-Bombo” in English vocabulary mastery: - Sri Ningsih; Wiputra Cendana; Elce Purwandari (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
Using games in an English class can enhance the student’s learning process. It offers an environment where the students can practice using new words and express themselves freely. This study aims to measure the effect of the traditional game the Konjo community “Äk’ Bombo-Bombo” in improving the student’s vocabulary mastery. The game is one of the popular traditional games in rural areas of the Kajang sub-district. Therefore, it is proper to be applied for students of elementary 115 in Tana Toa Village, Kajang. The study conducted a pre-experimental method with one group pre-test and post-test design. Independent and dependent variables were determined as the traditional game of Ak Bombo Bombo and the student’s English vocabulary development scores, respectively. There were 20 students in sixth grade in elementary school as the samples, which were chosen by using the total sampling technique. The results of this study showed that the student's mean post-test score (3.10) was higher than the pre-test score (3.05). Statistical tests also show that the value of the t-test, pre-test, and post-test is less than the alpha value (0.000 < 0.05). It can be concluded that the traditional game Ak Bombo-Bombo increased the student’s English vocabulary significantly in a positive way.